Evidence-based practice for nurses : appraisal and application of research - Schmidt, Nola A.; Brown, Janet M. (Burlington, MA : Jones & Bartlett Learning, 2025)
"Evidence-Based Practice for Nurses: Appraisal and Application of Research is an essential resource for teaching students how to translate research into practice. This text is built upon the foundation of the five step IDP process (knowledge, persuasion, decision, implementation, and confirmation), guiding students through the hierarchy of evidence while interweaving concepts such as the evolution of nursing science, quality improvement projects and how they relate to evidence-based practice, as well as search strategies and how to choose a specific research design"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Nursing Research -- methods; Evidence-Based Nursing